GlobSnow v3.0 Northern Hemisphere snow water equivalent dataset - Kari Luojus (Nature Portfolio, 2021)
Measurement(s) snow • snow mass • snow water equivalent Technology Type(s) satellite imaging Sample Characteristic - Environment cryosphere Sample Characteristic - Location Northern Hemisphere Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14336612